Supervisory styles and graduate student innovation performance: The mediating role of psychological capital and the moderating role of harmonious academic passion - Yang, Bingbing; Bao, Shuimei; Xu, Juan (Frontiers in Psychology, 2022)
Supervisory styles Are Key predictors of graduate students’ innovation performance (GSIP), but the mediating and moderating mechanisms underlying this relationship require further exploration. Based on the job demands-resources model and conservation of resources theory, this study analyzed the influence of supervisory styles on GSIP, including the mediating role of psychological capital (PsyCap) and the moderating role of harmonious academic passion (HAP). Questionnaires were completed by 400 graduate students from a Chinese university. The results indicated that (1) both supportive and directive supervisory styles (SSS and DSS) were positively related To GSIP, (2) PsyCap fully mediated the relationship between SSS and GSIP, and (3) HAP significantly moderated the effect of DSS but exhibited no moderating influence on the effect of SSS. These findings contribute to a deeper understanding of why, how and when supervisory styles influence GSIP. Implications for both theory and practice as well as the limitations of this research are discussed.